Decomposition of labor earnings: an analysis between metropolitan regions and non-metropolitan regions in Brazil - Jefferson Andronio Ramundo Staduto; Amarildo Hersen (European Regional Science Association (ERSA), 2010)
This paper aim at examining the dispersion of intra and inter-regional of principal labor earnings of the Metropolitan Regions (MR) and Non-Metropolitan Regions (NMR) of the States of Bahia, Ceará, Minas Gerais, Pará, Paraná, Pernambuco, Rio de Janeiro, Rio Grande do Sul and S\~ao Paulo, Brazil. It were applied the Chow structural test and decomposition of Oaxaca, and Heckman procedure. It was used data from the National Research by House Sample at 2006. The theoric approach was based on the Theory of Human Capital and Theory of Segmentation Labor Market. The results indicated that regional aspects and personal attributes of workers contributed for explaining the gap between labor earnings but were not homogeneous among States. Finally in the States that have highest Gross Domestic Product the regional effects were more important factors for explaining the differences for labor earnings among of MR and NMR.
Keywords: 330; wages dispersion; labor market; labor earnings; regional economy